Interventional Potential of Recombinant Feline Hepatocyte Growth Factor in a Mouse Model of Non-alcoholic Steatohepatitis - Yang, Yoon Mee; Fukui, Masato; Wang, Zhijun; Miao, Fiona; Karriker, Margo J.; Seki, Ekihiro (Frontiers in Endocrinology, 2018)
Background & Aims: Hepatocyte growth factor (HGF) is a multifunctional pleiotropic protein involved in tissue regeneration, protection, angiogenesis, anti-inflammatory and anti-fibrotic response, and tumorigenesis, through binding to its receptor MET. Recombinant HGF protein has been shown to mitigate various liver disease models, such as alcohol-induced liver injury, hepatic ischemia-reperfusion injury, and fibrosis. This study aimed to investigate the anti-inflammatory, anti-fibrotic, and anti-lipogenic effects of exogenous administration of feline HGF on a non-alcoholic steatohepatitis (NASH) mouse model. Methods: Wild-type C57BL/6 mice were fed choline-deficient amino acid defined (CDAA) diet for three weeks to create the mouse model of NASH, which displays hepatic steatosis, inflammation, injury, and very mild fibrosis. One mg/kg of recombinant feline HGF was administered intravenously daily in the last seven days of the total 3 weeks of CDAA diet feeding. Then, hepatic steatosis, inflammation, injury, and fibrogenic gene expression was examined. Results: After 3 weeks of a CDAA diet-feeding, the vehicle-treated mice exhibited evident deposition of lipid droplets in hepatocytes, inflammatory cell infiltration, and hepatocyte ballooning along with increased serum ALT levels whereas recombinant HGF-treated mice showed reduced hepatic steatosis, inflammation, and ballooned hepatocytes with a reduction of serum ALT levels. Recombinant HGF administration promoted hepatocyte proliferation. Increased hepatic lipid accumulation was accompanied by elevated expression of lipogenesis genes Fasn and Dgat1 in vehicle-treated mice. In HGF-treated mice, these genes were reduced with a decrease of lipid accumulation in the liver. Consistent with the anti-inflammatory property of HGF, augmented macrophage infiltration and upregulation of chemokines, Cxcl1, Ccl2, and Ccl5 in the CDAA diet-fed mice, were suppressed by the addition of the HGF treatment. Finally, we examined the fibrotic response. The vehicle-treated mice had mild fibrosis with upregulation of Col1a1, Acta2, Timp1, Tgfb1, and Serpine1 expression. Recombinant HGF treatment significantly suppressed fibrogenic gene expression and collagen deposition in the liver. Conclusion: Recombinant feline HGF treatment suppressed the progression of NASH in a CDAA diet feeding mouse model. This suggests that recombinant HGF protein has therapeutic potential for NASH.